Ahmed-i Dai'ye Atfedilen Yüz Hadis Tercümesi Üzerine - Çetin, Abdülbaki (Gökkubbe, 2004)
Ahmed-i Dâî, XIV. yüz yılın sonlarıyla XV. yüz yılın başlarında yaşamış bir müelliftir. Altısı manzum sekizi mensur olmak üzereş on dört eseri bilinmektedir. Bunlardan biri de Yuz Hadis Tercıimesi'dir. Bu makalede Ahmed-i Dili'ye ait olduğu iddia edilen Yuz Hadis Tercumesi'nin Erzurumlu Mustafa Darir'in Yuz Hadis Yıiz Hıkfıye adıyla bilinen eserinin bir nüshası olduğu ortaya konmuş ve eserin iki yeni nüshası haber verilmiştir. Ahmed-i Dai is a poet who lived at the end of the 14th century and the beginning of the 15th century. He has written fourteen works. Six of them are poetic and eight of them are prose works. One of them is "Translation of One Hundred Hadiths." This article determines that the manuscript, belived to be Ahmed-i Dai's Translation of One Hundred Hadiths, is indeed a copy of Mustafa Darir's One Hundred Hadit/ıs One Hundred Stories. In addition two new manuscripts of the work are introduced.
On Translation of One Hundred Hadiths Attributed to Ahmed-i Dai
Keywords: Ahmed-i Dâî; Yüz Hadis Tercümesi; Mustafa Darîr; Yüz Hadis Yüz Hikaye; Eski Anadolu Türkçesi; Translation of One Hundred Hadiths; One Hundred Hadiths One Hundred Stories; Old Anatolian Turkish